Association of Cardiovascular‐Kidney‐Metabolic Syndrome With Cognitive Decline and Dementia: The ARIC Study Insights - Peichen Xie; Yiqin Wang; Xinghao Xu; Li Tan; Xingdi Guo; Ziqi Xu; Rong Ye; Manhuai Zhang; Xiaodong Zhuang; Zhijian Li; Wei Chen; Xinxue Liao; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiovascular‐kidney‐metabolic (CKM) syndrome is an emerging clinical entity emphasizing the need for a holistic approach to patient care. The relationship between CKM syndrome and cognitive decline or dementia remains undetermined. Methods A total of 10 426 participants in the ARIC (Atherosclerosis Risk in Communities) study, classified into 4 CKM risk categories at baseline (visit 2: 1990–1992): low risk (≤5%), borderline risk (5%–7.4%), intermediate risk (7.5%–19.9%), and high risk (≥20%), were used to investigate the associations between CKM risk and cognitive decline or dementia using regression analysis. Results Elevated CKM risk level is significantly associated with increased risks of cognitive decline and dementia incidence. Each 1‐unit increase in CKM risk level is linked to a 6% higher risk of dementia progression in the fully adjusted model. Conclusions These findings highlight a strong association between CKM syndrome and cognitive decline or incident dementia, underscoring the importance of early interventions.